Adaptive Pixel-Selection Fractional Chaotic Map Lattices for image cryptography - Sittigorn Jirasak; Paithoonwattanakij Kitti (My University, 2015)
Chaotic theory has been employed in cryptography application for establishing a sequence of data closest to pseudorandom number. Image cryptography with Chaotic Map Lattices (CML) uses the chaos parameters, the number of iterations and the number of cycles for encryption as secret keys. Amount of secret keys has a great impact on security in cryptography. Adaptive Pixel-Selection Fractional Chaotic Map Lattices (APFCML) enhances the encryption security by introducing a novel non-integer fractional order concept as secret keys. Fractional chaos is modified chaos with a fractional differential equation containing derivatives of non-integer order. A non-integer order has an effect on the range of chaos's parameter. Moreover, the encryption sequence has been adaptively selected based on another chaos generator. In the experiments, the measurement indices of originality preservation, visual inspection, and statistical analysis are used to evaluate the performance of the proposed APFCML compared to that of the original CML.   Key words: Chaotic, fractional logistic, image cryptography, Lyapunov exponent, bifurcation diagram. &nbsp
Keywords: Logistic map; Chaos-based Image/Signal Encryption